Breeding apomictic bahiagrass (Paspalum notatum Flügge) with improved turf traits. (7th March 2017) - Rios, Esteban; Kenworthy, Kevin; Blount, Ann; Quesenberry, Kenneth; Unruh, Bryan; Erickson, John; Altpeter, Fredy; Munoz, Patricio
Abstract: The development of a turf‐type bahiagrass could have a remarkable impact on the billion‐dollar turf industry in the south‐eastern United States. The goals of this study were to (i) select bahiagrass genotypes with improved turf attributes and (ii) determine the reproductive mode and seed fertility of selected genotypes. The population included mutants, wild types, hybrids and standard cultivars evaluated at two locations for two years. Morphological variation was observed and clonal repeatability ( H 2 ) ranged from 0.27 to 0.90. Flowering was extremely reduced in some mutants, which also exhibited dark green colour, finer texture and reduced canopy height. Cytoembryological observations revealed that diploids reproduced sexually and tetraploids by obligate or facultative apomixis. Genotypes with superior seed fertility were identified, while others were comparable to the standard cultivars. While mutant plants exhibited great morphological variation, the random mutations did not affect their reproductive mode, validating the use of mutagenesis in apomictic species. The high H 2 indicated that selection for improved turf attributes could be successfully performed with the advantage of clonal seed propagation.